Fencing in AIDS Gender, Vulnerability, and Care in Papua New Guinea (Edition 1) - Wardlow, Holly (University of California Press, 2020)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. In this vitally important book, medical anthropologist Holly Wardlow takes readers through a ten-year history of the AIDS epidemic in Tari, Papua New Guinea, focusing on the political and economic factors that make women vulnerable to HIV and on their experiences with antiretroviral therapy. Alive with the women's stories about being trafficked to gold mines, resisting polygynous marriages, and struggling to be perceived as morally upright, Fencing in AIDS demonstrates that being female shapes every aspect of the AIDS epidemic. Offering crucial insights into the anthropologies of mining, ethics, and gender, this is essential reading for scholars and professionals addressing the global AIDS crisis today.